Clinical characteristics, referral patterns and time to recovery in youth and adults following a sport-related concussion (src). Issue 11 (25th May 2017) - MacGregor, Katie; Atkins, Christine; Blake, Tracy; Ziel, Micah; Schneider, Kathryn
Abstract : Objective: To describe the clinical characteristics, referral patterns and time to recovery in an acute sport-related concussion (SRC) clinic population. Design: Prospective Case Series Setting: Acute Sport Concussion Clinic (ASCC) Participants: Patients aged 13-60 years seen within 4 weeks of SRC at the ASCC from September 2015–April 2016. Outcome measures: Frequency, proportions, medians and interquartile ranges (IQR) were used to describe sex, age group, time from injury to assessment, referral sources, time to recovery (days), referrals to additional services, and attrition. Results: ASCC assessments were requested by 111 patients a median of 9 days (IQR:4-17) post-concussion [33% female; 60 children [median age 15 years (IQR:14-16)], 51 adults [median age 31 years (IQR:21-42)]; attrition rate=10%]. Referral sources included: self-referral [n=94 (85%)], emergency department [n=9 (8%)], primary care physician [n=7 (5%)], and athletic therapist (n=1). Initial assessment occurred a median of 7 days (IQR:2-9) following the evaluation request. Patients underwent a standardised assessment including symptom scores, neurological, cervical spine and vestibulo-ocular screening a median of 17 days (IQR:9-25) post-concussion. There were 94 (85%) patients with clinical findings of cervical spine and/or vestibulo-ocular dysfunction. Treatment was received by 71/94 (76%) of patients with observed dysfunction. Medical clearance to return to play occurred a median of 30 days (IQR:21-107) post-concussion (n=51) . Conclusions: A novel direct-access clinic specific to SRC assists in early triage, leading to expedited assessment, management and treatment in the early post-concussion period. Focused assessment assists in management and recovery with accelerated referral to appropriate services. Competing interests: None.